Experiments on Hybrid Precast Concrete Shear Walls Emulating Monolithic Construction with Different Amounts of Posttensioned Strands and Different Debond Lengths of Grouted Reinforcements - Zhangfeng Zhu; Zhengxing Guo (Advances in Materials Science and Engineering)
This paper proposed a hybrid precast concrete shear wall emulating monolithic construction (HPWEM) that utilized grouted vertical connecting reinforcements and unbonded posttensioned high-strength strands across the horizontal joint for the lateral resistance. The grouted reinforcements with predetermined debond length were used to provide strength by tension and energy dissipation by yielding. The posttensioned strands were mainly employed to offer the restoring force to reduce the residual displacement by elastic extension. The overlapping welded closed stirrups improved the confinement property of the restrained concrete, avoiding the brittle failure. Six HPWEM specimens, considering variables including the amounts of strands and the debond lengths of grouted reinforcements, as well as one referenced cast-in-place monolithic wall specimen, were tested under the low-cycle reversed lateral load. The HPWEM specimens were capable of providing strength, stiffness, ductility, and energy dissipation equivalent to that of the monolithic wall specimen under certain variable condition.